Measuring the Biopsychosocial Health of Emergency Medical Technicians in Tehran, Iran - Vahid Delshad; Hamidreza Khankeh; Abbas Ebadi; Mariola Bidzan; Gholamreza Ghaedamini Harouni; Marcus Stueck (Health in Emergencies & Disasters Quarterly)
Background: Emergency medical technicians (EMTs) should have good socioeconomic status and health status so that people in need can benefit from their services. The present study aims to measure the biopsychosocial health of EMTs in Tehran, Iran. Materials and Methods: This is a descriptive cross-sectional study. The study population consists of the EMTs from six regions of Tehran, Iran. Of these, 563 EMTs were included in the study. Stueck et al.’s health cube battery (HCB) tool, which has six domains of individual resources, external resources, workload, stress consequences, biocentric performance, and socioeconomic status, was used to collect data online. The physiological reactions (blood pressure, pulse rate, and oxygen saturation) were assessed based on three levels of socioeconomic status (low, moderate, and high). The data analysis was performed in Excel and SPSS software, version 22. Results: The mean age of participants was 31.88±43.6 years, and their mean work experience ranged from 1 to 30 years (mean=14.7±73.5 years). The mean score for biocentric performance was higher than that of other domains. The mean levels of physiological reactions were within the normal range. Overall, 50% (n=281) had moderate socioeconomic status. There was no significant difference in terms of physiological conditions among the three socioeconomic groups. Conclusion: The EMTs with better socioeconomic status have better performance and physiological status. There is a need for more attention to the socioeconomic status of EMTs in Tehran, which has a direct impact on their performance and an indirect effect on their physiological health.